IMPLEMENTATION ANALYSIS OF DYNAMIC REAL OPTIONS METHOD AND ITS COMPARISON WITH CONVENTIONAL DISCOUNTED CASH FLOW METHOD IN ECONOMIC EVALUATION OF THE OIL FIELD DEVELOPMENT PROJECT - HADIWARATAMA INDRAJAYA (NIM : 22216013 ), TB
The current economic evaluation of oil field development projects is still widely carried out by using the conventional discounted cash flow (DCF) method. However, the deficiencies of conventional DCF methods that are static and cannot take into account the uncertainty, can cause a company to make systemic errors in a project evaluation and obtain an unrealistic NPV value. The real options (RO) method is an alternative project valuation method that can correct the shortcomings of conventional DCF methods where uncertainty are calculated in a way that better represents the actual conditions.In the RO method, the risk caused by uncertainty is compensated directly on the source of the variable that causes uncertainty. In this research study, the dynamic RO method will be implemented with monte carlo simulation in an economic evaluation of the oil field development project with a case study on field X in Indonesia. The project valuation will be modeled by using a monte carlo simulation that allows companies to see the value of cash flows and NPVs that move dynamically according to the probababilty of the uncertainty simultaneously. Fluctuations in oil prices are assumed to be the only factor that can cause a risk of uncertainty to the future cash flows and project value. Based on the analysis, it can be seen that based on the cumulative distribution probability curve of the NPV value generated by the dynamic RO method, the NPV value generated by the conventional DCF method is at a confidence level above P80. This represents that the NPV value produced by the conventional DCF method is considered very pessimistic.